2023
DOI: 10.3389/fphar.2023.1215861
|View full text |Cite
|
Sign up to set email alerts
|

Aminooxy acetic acid suppresses Th17-mediated psoriasis-like skin inflammation by inhibiting serine metabolism

Abstract: Background: Psoriasis is a common chronic inflammatory skin disease characterized by an external red rash that is caused by abnormal proliferation and differentiation of keratinocytes and immune T cells. This study aimed to elucidate the role of aminooxy acetic acid (AOA) in alleviating psoriasis from the perspective of immunology and metabolomics. Therefore, contributing to the development of new drugs as candidates for psoriasis treatment.Methods: To investigate the symptom-alleviating effects and the relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Total RNA was extracted from cultured cells and frozen tissues using the RNAIso Plus Reagent (Takara, Tokyo, Japan) according to the manufacturer’s instructions. cDNA synthesis and RT-qPCR analyses were performed as described previously ( 42 ). The RNA samples were dissolved in RNase-free water (Thermo Fisher Scientific) and purified by phenol/chloroform extraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from cultured cells and frozen tissues using the RNAIso Plus Reagent (Takara, Tokyo, Japan) according to the manufacturer’s instructions. cDNA synthesis and RT-qPCR analyses were performed as described previously ( 42 ). The RNA samples were dissolved in RNase-free water (Thermo Fisher Scientific) and purified by phenol/chloroform extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lysates were prepared and western blotting was performed as described previously ( 42 ). Proteins were separated using 6%, 10%, or 12% sodium dodecyl sulfate-polyacrylamide gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…Metabolomics also provides new ideas for the treatment of psoriasis. In mice, aminooxy acetic acid (AOA) could alleviate psoriasis symptoms by impacting the Th17-associated passway, suggesting a new therapeutic target [ 106 ]. Chen et al found that a higher level of L-carnitine (LC(C0)) can reduce skin thickness and Th17 infiltration in IMQ-induced mice, suggesting that supplementing with LC(C0) could be a viable therapeutic approach for treating psoriasis [ 107 ].…”
Section: Metabolomicsmentioning
confidence: 99%
“…The pathogenesis of psoriasis is complex and multifactorial, involving genetic predisposition, immunological dysregulation, and environmental triggers. Recent advances in understanding the pathophysiology of psoriasis have highlighted the role of T-helper cells, particularly Th17 cells ( Guo et al, 2023 ; Lee et al, 2023 ), in driving the inflammatory cascade that characterizes this disease.…”
Section: Introductionmentioning
confidence: 99%